ENHANCING PERFORMANCE OF SCHOOL PUBLIC RELATIONS: THE CONTRIBUTING WEBSITE OF SCHOOL PUBLIC RELATION SERVICES IN MADRASAH TSANAWIYAH - Anif Solikhin; Giyoto; Kholilul Rokhman (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2022)
Public relations problems at Madrasah Tsanawiyah 1 Klaten are still lacking in promoting school achievements, the need for more productive school relations, student guardians, and society. Public Relations has not been able to establish active communication between teachers and students outside of school. The research aimed to discover innovation in education public relations management through websites, public relations models, and the benefits of public relations management. This research uses a qualitative approach in the form of a case study. The innovation in public relations activities through website-based information technology facilities. The results of this study indicate that the school has carried out educational public relations innovations by managing the website. The website management was managed by a team with the Decree of the Madrasah Head. Website content includes models and forms of education public relations communication through websites still classified as public information models. This model of public relations has paid attention to the importance of correct information but has not been based on research and has not provided an opportunity to provide feedback from the website reader community. The results of the research impact school achievement being known by the community, and active communication are established between schools, parents of students, and the community.